2011
DOI: 10.1186/1471-2407-11-437
|View full text |Cite
|
Sign up to set email alerts
|

A gene signature in histologically normal surgical margins is predictive of oral carcinoma recurrence

Abstract: BackgroundOral Squamous Cell Carcinoma (OSCC) is a major cause of cancer death worldwide, which is mainly due to recurrence leading to treatment failure and patient death. Histological status of surgical margins is a currently available assessment for recurrence risk in OSCC; however histological status does not predict recurrence, even in patients with histologically negative margins. Therefore, molecular analysis of histologically normal resection margins and the corresponding OSCC may aid in identifying a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
107
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(114 citation statements)
references
References 45 publications
6
107
1
Order By: Relevance
“…Microarray-based expression profiling of unmatched normal mucosa, primary tumors, lymph node metastases, and recurrent HNSCC lesions identified mRNA expression signatures predictive of metastasis and recurrence, but the clinical impact of these observations remains unrealized (20)(21)(22)(23). Only one study included analysis of patientmatched index primary tumors and synchronous nodal metastases; this found that the expression profiles of primary tumors were largely preserved in their respective metastatic lymph nodes (23).…”
Section: Introductionmentioning
confidence: 99%
“…Microarray-based expression profiling of unmatched normal mucosa, primary tumors, lymph node metastases, and recurrent HNSCC lesions identified mRNA expression signatures predictive of metastasis and recurrence, but the clinical impact of these observations remains unrealized (20)(21)(22)(23). Only one study included analysis of patientmatched index primary tumors and synchronous nodal metastases; this found that the expression profiles of primary tumors were largely preserved in their respective metastatic lymph nodes (23).…”
Section: Introductionmentioning
confidence: 99%
“…ITGA2, ITGA3 and ITGAV, members of the integrins, are invasion-related genes (28,29). Integrins are transmembrane adhesion molecules that mediate cell-cell and cell-extracellular matrix attachment.…”
Section: Discussionmentioning
confidence: 99%
“…Expression datasets of human cell line were excluded in the study. The included GEO datasets (GSE) are shown in Table 1 (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Methodsmentioning
confidence: 99%